2018
DOI: 10.1089/aid.2018.0115
|View full text |Cite
|
Sign up to set email alerts
|

TAX-mRNA-Carrying Exosomes from Human T Cell Lymphotropic Virus Type 1-Infected Cells Can Induce Interferon-Gamma ProductionIn Vitro

Abstract: Human T cell lymphotropic virus type 1 (HTLV-1) is the etiological agent of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and adult T cell leukemia/lymphoma. The development of HAM/TSP, a chronic neuroinflammatory disease, is correlated to complex interaction between the host immune response and the infecting virus. Tax expression plays an important role in HAM/TSP pathogenesis by activating various cellular genes, including the cytokines interferon-gamma (IFN-γ) and tumor necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
4
16
0
Order By: Relevance
“…The presence of Tax in EVs are in line with previous findings of EV associated Tax in cell lines, PBMCs, and CSF from HAM/TSP patients (Jaworski et al, 2014a; El-Saghir et al, 2016; Barclay et al, 2017a; Anderson M.R. et al, 2018; Otaguiri et al, 2018). Moreover, they show that an IR treated infected cell may potentially contain significantly higher levels of intracellular Tax.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of Tax in EVs are in line with previous findings of EV associated Tax in cell lines, PBMCs, and CSF from HAM/TSP patients (Jaworski et al, 2014a; El-Saghir et al, 2016; Barclay et al, 2017a; Anderson M.R. et al, 2018; Otaguiri et al, 2018). Moreover, they show that an IR treated infected cell may potentially contain significantly higher levels of intracellular Tax.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the proinflammatory cytokines, IFN-γ and TNF-α, were detected in healthy PBMCs after exposure to EVs isolated from HTLV-1-infected cells. This finding indicates that EVs containing Tax mediate the release of these two cytokines and the activation of T helper 1 (Th1) immune response in the treated PBMCs [109]. This finding could explain the inflammation which is predominantly seen in HAM/TSP patients with Th1 phenotype [110].…”
Section: Ev Cargo In Viral Infectionmentioning
confidence: 85%
“…HTLV-1 is the causative agent of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and adult T-cell leukemia/lymphoma [63][64][65]. The transactivator protein Tax expressed by HTLV-1 affects many critical cellular pathways, including host cell DNA damage response mechanisms, cell cycle progression, apoptosis, and proinflammatory cytokines [63,64].…”
Section: Exosomes and Other Enveloped Virusesmentioning
confidence: 99%
“…HTLV-1 is the causative agent of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and adult T-cell leukemia/lymphoma [63][64][65]. The transactivator protein Tax expressed by HTLV-1 affects many critical cellular pathways, including host cell DNA damage response mechanisms, cell cycle progression, apoptosis, and proinflammatory cytokines [63,64]. Recent results showed that the exosomes derived from HTLV contain functional HTLV-1 proteins (such as Tax protein) and mRNAs (tax, HBZ, and Env mRNAs), which can be transferred to recipient cells by exosome and stimulate the production of proinflammatory cytokines, such as IFN-γ, IL-6, and TNF-α, and T helper (Th) 1 -immune response [63,64,66,67].…”
Section: Exosomes and Other Enveloped Virusesmentioning
confidence: 99%
See 1 more Smart Citation